Application of Edible Coating to Extend Shelf Life of Custard Apple (Annona Squamosa) Fruit during Storage - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Custard apple (Annona squamosa L.) is a climacteric fruit and highly perishable in nature. The fruit is well known for its sweet taste, specific flavour, and pleasant, aromatic creamy pulp. The fresh fruit pulp contains high nutritional value such as protein, carbohydrate, sugar, vitamin and mineral. Edible coatings are widely used for extension of shelf life of fruits and vegetables by reduction of moisture loss and gas exchange as well as reduction of the physiological disorders. The main problem of postharvest losses associated with custard apples is rapid loss of firmness. The objective of the present study was to identify the effect of different xanthan gum concentrations (1%, 2%, 3%, 4%, 5%) and storage temperature (8 oC, 12 oC, 16 oC, 20 oC) to the weight loss, firmness, total soluble sugar and ascorbic acid in custard apple (Annona squamosa) fruits during preservation. Moreover, shelf life (0 day, 7 days, 14 days, 21 days and 28 days) of custard apple (Annona squamosa) fruit in storage also clarified. Results demonstrated that xanthan gum 4% and storage temperature 8 oC could maintain custard apple (Annona squamosa) fruit quality for 28 days without any deterioration. This is an opportunity to develop value‐added products reducing the postharvest losses, improving nutritional value and generating additional revenue for custard apple growers.Keywords: Custard apple, Xanthan gum, Coating, Firmness, Shelf life, Preservation.